A Novel NOD2-associated Mutation and Variant Blau Syndrome: Phenotype and Molecular Analysis. (2nd January 2018) - Ebrahimiadib, Nazanin; Samra, Khawla Abu; Domina, Aaron M.; Stiles, Ethan R.; Ewer, Roger; Bocian, Charlie P.; Foster, C. Stephen
ABSTRACT: Purpose : To describe the clinical and molecular implications of a novel mutation in the NOD2/CARD15 gene on a family and its seven affected members. Methods : We reviewed the clinical presentations of family members who came to our center for refractory uveitis. Genetic testing and molecular testing was performed. Results : All affected members had adult onset recurrent non-granulomatous panuveitis. The inheritance pattern suggested an autosomal dominant disease and genetic analysis identified a novel mutation in the NOD2 gene that converted amino acid 600 from glutamate to alanine (E600A). Transfection of the E600A NOD2 into human embryonic kidney-293 (HEK293) cells revealed constitutive activation and a reduced ability to respond to the NOD2 ligand, muramyl dipeptide (MDP) as compared with wild-type NOD2. Conclusions : The E600A mutation in the NOD2 gene may confer a higher penetrance of uveitis but a later onset of milder forms of non-ocular involvement.